Changes to polychlorinated biphenyl (PCB) signatures and enantiomer fractions across different tissue types in Guillemots. (June 2018) - Megson, David; Brown, Thomas A.; O'Sullivan, Gwen; Robson, Matthew; Ortiz, Xavier; Worsfold, Paul J.; Comber, Sean; Lohan, Maeve C.; Reiner, Eric J.
Abstract: Two Guillemot carcases were dissected, each providing 12 discrete tissue samples and 3 samples of partially digested food. One hundred and five PCBs from the 209 PCBs determined by GCxGC-ToFMS were detected. The relative proportions of individual PCBs did not vary greatly within tissue types, although the PCB profile from undigested food could be distinguished. Enantiomer fractions (EFs) were determined for CB-95, CB-136 and CB-149 by GC-HRqToFMS. EFs in the partially digested food were near racemic, with high levels of enrichment for E1 CB-95 in the kidneys and liver (EF of 0.80 and 0.84 respectively). This provides some of the clearest evidence to date that fractionation takes place in the organs where metabolic biotransformation and elimination of PCBs occurs. Our findings also confirm the ability of non-lethal sampling techniques, such as collection of small (<1 g) blood samples, to provide PCB signatures that are representative of an individual organism. Highlights: Over 100 different PCBs identified in Guillemot tissue PCB profile consistent across 12 different tissue types Enantiomer fractionation of CB-95 detected in kidney and liver Non-lethal sampling techniques (1 mL blood) produce representative PCB signatures